Romeo & Juliet - "Shakespeare, William" (Sweet cherry publishing: China, 2013)
Hailed as one of the greatest romantic tragedies ever written, William Shakespeare s Romeo and Juliet is the tragic love story of the star-crossed lovers , Romeo and Juliet. Set in the city of Verona, Italy, the play revolves around the feud between two affluent families, the Montagues and the Capulets. Despite the enmity, Romeo Montague and Juliet Capulet fall passionately in love and wed in secret. However, the curse of enmity overpowers and everything goes terribly wrong. This short narrative version of the play has been suitably adapted to help introduce the play to young readers. It can be read by children or read to them by parents who wish to introduce them to the play. It can also be used by teachers as a classroom resource. The easy-to-read narration and comic-style illustrations are sure to captivate children s interest and develop their reading skills
Keywords: Adaptations Juvenile literature